Efficacy of interferon‐beta plus ribavirin combination treatment on the development of hepatocellular carcinoma in Japanese patients with chronic hepatitis C. Issue 3 (2nd September 2015) - Ikezaki, Hiroaki; Nomura, Hideyuki; Furusyo, Norihiro; Ogawa, Eiichi; Kajiwara, Eiji; Takahashi, Kazuhiro; Kawano, Akira; Maruyama, Toshihiro; Tanabe, Yuichi; Satoh, Takeaki; Nakamuta, Makoto; Kotoh, Kazuhiro; et al.
Abstract: Aim: Although there is much evidence of an antitumor effect of pegylated interferon (IFN)‐α‐based treatment, limited data is available about that of IFN‐β‐based treatment. Our goal was to evaluate the impact of IFN‐β plus ribavirin (RBV) treatment on the suppression of hepatocellular carcinoma (HCC). Methods: This retrospective, multicenter study consisted of 124 chronic hepatitis C patients who were treated with IFN‐β plus RBV treatment, including 61 with advanced fibrosis and five with pretreatment HCC. All participants were followed for a median of 2.8 years (range, 2.2–3.2) after the end of their antiviral treatment. The data of 112 patients who finished the treatment were available for analysis. Cox proportional hazard analyses were performed to determine factors significantly associated with HCC development. Cumulative incidence curves for HCC were plotted using the Kaplan–Meier method and differences between groups were assessed using the log–rank test. Results: The 2.9% rate of HCC development of patients with sustained virological response (SVR) was significantly lower ( P  = 0.027) than the 15.9% of non‐SVR patients. Interestingly, no significant difference was observed between the rates of HCC development of patients with and without advanced fibrosis ( P  = 0.733), even though the SVR rate of patients with advanced fibrosis was significantly lower than that of those without advanced fibrosis ( P  < 0.001). Stepwise multivariable Cox analysis extracted that only SVR was significantly associated with HCC development (hazard ratio, 0.20; 95% confidence interval, 0.03–0.84, P  = 0.027). Conclusion: SVR was significantly associated with a lower risk of HCC development after IFN‐β plus RBV treatment.